The Inclusion of Flour Curcuma(Curcuma xanthorriza Roxb) and Red Ginger Flour (Zingiber officinale var rubrum) in the Diets with Different levels on Carcass Yields and Immunity Organs of male laying hens - Suanta, I Made; Hafsah, Hafsah; Gobel, Minarni (Universitas Tadulako, 2021)
This study aimed to determine the effect of inclusion of curcuma and red ginger flour in the diets on slaughter weight, carcass (carcass and non-carcass components), meat quality (protein and fat) and immune organs of male laying hens. The research was carried out at the Teaching Farm, Faculty of Animal Husbandry and Fisheries, Tadulako University, South Sibalaya Village, Tanambulava District, Sigi Regency. This study was conducted for 7 weeks, March 4 - April 26, 2020. The study used DOC 168 male laying hens which were reared until the age of 54 days, than weighed to obtain slaughter weights for observation the carcass, meat quality, and immunity. The treatments were designed using Completely Randomized Design (CRD) with 7 treatments and 4 replications. The treatments were: Po = 100% basal diets, P1 = 0.5% curcuma flour + 99.5% basal diets, P2 = 1% curcuma flour + 99% basal diets, P3 = 1.5% curcuma flour + 98.5 % basal diets, P4 = 0.5% red ginger flour + 99.5% basal diets, P5 = 1% red ginger flour + 99% basal diets, P6 = 1.5% red ginger flour + 98.5% basal diets. Data were analyzed using ANOVA according to the research design applied. The results were shown high significant effect (P<0.01) on slaughter weight, carcass percentage, breast carcass components, immune organs (liver) and meat quality (protein and fat), and had a significant effect (P<0, 05) on carcass components ( thighs) and non carcass components (legs). The highest slaughter weight and carcass percentage were obtained from treatment P6 (red ginger flour with a level of 1.5% in the diets). The conclusion of this research that the inclusion of curcuma and red ginger flour can be applied in the diets up to 1.5% in male laying hens feed.